PENGEMBANGAN KOMIK EDUKATIF UNTUK MENGAJARKAN ETIKA KOMUNIKASI ISLAM DI SDIT AL-FIRDAUS - Faza Sabila Firdaus; Mila Hanifah; Nurfaizah Nurfaizah; Yauma Wulida Farhana (JIP: Jurnal Ilmu Pendidikan, 2025)
This research aims to develop educational digital comics that teach Islamic communication ethics to students at SDIT Al-Firdaus. Using a Research and Development approach, this research analyzes how comics that are adapted to students' cognitive levels are able to deepen their understanding of the ethical values ​​of communication and increase motivation and participation in learning compared to conventional methods. This study is based on several theories, such as learning media theory, communication ethics theory, and the social construction of reality, and includes a review of literature related to comic media in character and ethics education. The data analysis method used is validity analysis using scoring criteria and Aiken's V index. Based on the validation test, the results show that the feasibility of the learning materials and media reached a validity value of 0.8, which falls into the "High" category or is deemed suitable for use.